O esvoaçar de lembranças no pouso de lutas socioambientais de mulheres negras - Souza, Cássia Fabiane dos Santos (2019)
This research is part of the project "International Network of Researchers in Environmental Education and Climate Justice (REAJA - Fapemat)", which assumes five major research goals in: i) climate justice; ii) culture of local dimensions; iii) capacity building processes; iv) communication and art; v) public policies. The project accepts that although climate change affects all the inhabitants of the Earth, there are social groups in more situations of vulnerability. Thus, as a research objective, I sought to know the life narratives of 11 black women, who, although they are mostly teachers, work in different social sectors. Through the sensitive listening of the narratives, I required to know the forms of ethnic-racial struggles, and in what way the climatic dimension was associated with this action. In other words, I tried to interpret the movements of these women, and if the climatic agenda was perceived in their struggles, or if they inserted in their daily life practices of a pedagogy that, explicitly or even veiled, are learning to build sustainable societies. Adopting the epistemology and praxis of Gaston Bachelard and Michèle Sato, the elements of water, earth, fire and air are the metaphors that deepen phenomenology in order to appreciate how climatic justice is inscribed in the narratives of 11 black women. In their stories of injustice, these people understand that race is more immediate in their challenges, yet the environmental dimension is widely perceived in the mazes of their lives. They cite cases of environmental racism, perceive water as a vital element in their daily lives and recognize the value of education in the processes of building more just and inclusive public policies. In the biographies of these women, the dimensions of militancy, gender, race, environment and education are like paints that shade the same pedagogical fabric. They are brushes that move in the memories painting the culture and the nature in permanent learning inside and outside the schools. However, in global and local societies, there is a lack of scientific information on climate justice. For that reason, I dared to frame the investigative screen participating in formative processes in Mata Cavalo, a “quilombo” of residence of two interviewees. With the help of the artist Gildásio Jardim, I show the processes of formation as important means of communicating the climate. I support the thesis that environmental education can enrol in people's lives, painting screens that denounce the injustices of situations of climate vulnerability, but above all, they are languages that announce a hope with shapes, colours and textures that allow the relief of life.